Experimental Infection of Taenia saginata eggs in Bali Cattle: Distribution and Density of Cysticercus bovis - Sadra Dharmawan, Nyoman; Damriyasa, I Made; Kapti, I Nengah; Sutisna, Putu; Okamoto, Munehiro; Ito, Akira (Jurnal Veteriner; Vol 10 No 4 (2009), 2009)
The objective of this study was to observe the development, distribution, and infection density of Taenia saginata metacestodes in Bali cattle. Three Bali cattle were experimentally infected with T. saginata eggs which were collected from taeniasis patients. The experimental animal was inoculated with : i) 1000,00 T. saginata; ii) 500,000 eggs; and iii) 1,000,000 eggs, respectivelly 100,000 (cattle 1), 500,000 (cattle 2), and 1,000,000 (cattle 3) T. saginata eggs, respectively. To observe the development of cysticerci, all cattle were slaughtered at 24 weeks post infection. To observe their distribution and density, slicing was done to the cattle?s tissues. The study results showed that cysts were found distributed to all muscle tissues and some visceral organs such as heart, diaphragm, lungs, and kidney of the cattle infected with 100,000 and 500,000 T. saginata eggs. Density of the cyst was in the range of 11 to 95 cysts per 100 grams of tissue. The highest density was noted in the heart (58/100 grams) and in diaphragm (55/100 grams). This study has confirmed that T. saginata eggs derived from taeniasis patient in Bali, if infected to Bali cattle can develop and spread to all muscle tissues and some visceral organs. From this study it was concluded that it is necessary to include the heart in the meat inspection at slaughter house for possibility of T. saginata cyst infection.$?
Keywords: T. saginata cyst; Bali cattle; experimental infection